Drug therapy: dose-response relationship of oral mesalazine in inflammatory bowel disease - C. J. J. Mulder; S. J. Van Den Hazel (Mediators of Inflammation)
Mesalazine is widely used in the treatment of inflammatory bowel disease. Little is known about the doseresponse relationship and about possible dose related side effects. In ulcerative colitis higher dosages of mesalazine (3 g) are more effective in maintaining a remission than lower dosages (1.5 g). In mild to moderately active ulcerative colitis, studies also indicate that higher dosages might be more effective in inducing remission. Dose-comparing studies in Crohn's disease are even more sparse, but the available results indicate higher efficacy at higher dose levels.